Tropical Forests and the Human Spirit : Journeys to the Brink of Hope. - Stone, Roger D. (University of California Press, 2001)
Tropical forests are vanishing at an alarming rate. This book, based on extensive international field research, highlights one solution for preserving this precious resource: empowering local people who depend on the forest for survival. Synthesizing a vast amount of information that has never been brought together in one place, Roger D. Stone and Claudia D'Andrea provide a clearly written and energizing tour of global efforts to empower community-based forest stewards. Along the way, they show the fundamental importance of tropical forest ecosystems and deepen our sense of urgency to save the.